Composition and divergence of coronavirus spike proteins and host ACE2 receptors predict potential intermediate hosts of SARS‐CoV‐2 - Liu, Zhixin; Xiao, Xiao; Wei, Xiuli; Li, Jian; Yang, Jing; Tan, Huabing; Zhu, Jianyong; Zhang, Qiwei; Wu, Jianguo; Liu, Long (Journal of medical virology, 2020)
From the beginning of 2002 and 2012, severe respiratory syndrome coronavirus (SARS‐CoV) and Middle East respiratory syndrome coronavirus (MERS‐CoV) crossed the species barriers to infect humans, causing thousands of infections and hundreds of deaths, respectively. Currently, a novel coronavirus (SARS‐CoV‐2), which has become the cause of the outbreak of Coronavirus Disease 2019 (COVID‐19), was discovered. Until 18 February 2020, there were 72 533 confirmed COVID‐19 cases (including 10 644 severe cases) and 1872 deaths in China. SARS‐CoV‐2 is spreading among the public and causing substantial burden due to its human‐to‐human transmission. However, the intermediate host of SARS‐CoV‐2 is still unclear. Finding the possible intermediate host of SARS‐CoV‐2 is imperative to prevent further spread of the epidemic. In this study, we used systematic comparison and analysis to predict the interaction between the receptor‐binding domain (RBD) of coronavirus spike protein and the host receptor, angiotensin‐converting enzyme 2 (ACE2). The interaction between the key amino acids of S protein RBD and ACE2 indicated that, other than pangolins and snakes, as previously suggested, turtles (Chrysemys picta bellii, Chelonia mydas, and Pelodiscus sinensis) may act as the potential intermediate hosts transmitting SARS‐CoV‐2 to humans. Highlights The critical residues of S protein RBD binding with ACE2 indicated the potential intermediate hosts transmitting SARS‐CoV‐2 to humans.